Comparison effect of high-intensity interval training and moderate intensity continuous training on vascular function in a mouse model of lower extremity peripheral artery disease - Slobodan Kojic; Steeve Menetrey; Karima Bouzourène; Lucia Mazzolai; Anne-Christine Peyter; Nathalie Rosenblatt-Velin; Grégoire P. Millet; Maxime Pellegrin (Bern Open Publishing, 2024)
Introduction Lower extremity peripheral artery disease (PAD), due to narrowing of the arteries supplying the legs, represents a major cause of physical disability. Exercise training is an important part of PAD treatment, improving functional capacity. Recent research suggests that exercise training-induced endothelial function improvement is involved in the benefits of exercise in PAD (Lee et al., 2023); however, the underlying molecular mechanisms remain unknown. In addition, the potential vascular benefits of high intensity training in PAD remain unexplored. Therefore, the aim of the study was to compare the effects of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) on endurance capacity, vascular endothelial function and expression of genes related to nitric oxide (NO) bioavailability in a mouse model of PAD. Methods PAD disease model was generated in male C57BL/6 mice by ligation of the right iliac artery. Mice with PAD were divided into 3 groups: sedentary control group (SED), MICT (40 min running at 70% of maximal aerobic speed) and HIIT (8 intervals of 2.5 minutes running at 90% of maximal aerobic speed combined with 2.5 minutes of running at 50% of maximal aerobic speed). Mice were exercised three times per week for 8 weeks. Maximal running time was determined by an incremental test until exhaustion. Vascular reactivity was assessed by measuring vasoconstrictor responses to phenylephrine as well as endothelium-dependent and -independent vasodilator responses to acetylcholine and DEA-NONOate, respectively, in isolated aortic rings. Gene expression of antioxidant enzymes (catalase and superoxide dismutase isoforms), prooxidant NADPH oxidase subunits (p22phox and p47phox), enzyme involved in NO production (endothelial NO synthase), vascular smooth muscle cell relaxation (soluble guanylate cyclase) and receptors involved in vascular tone regulation (a1 and b2 adrenergic receptors) was determined in aortic tissue by qPCR. Results Maximal running time was improved in both MICT and HIIT as compared to SED at the end of the study, but with no significant difference between the two exercise groups. Phenylephrine-induced vasoconstriction as well as vasodilator responses to acetylcholine and DEA-NONOate were significantly improved in MICT compared to SED while no significant differences were reported between HIIT and SED. There was no significant difference in gene expression among the three groups. Discussion/Conclusion MICT and HIIT were equally effective at improving endurance capacity in mice with PAD. However, only MICT improved vascular reactivity. References Lee, J., Zarezadehmehrizi, A., LaVoy, E., Markofski, M., & Park, Y. (2023). Exercise training improves brachial artery endothelial function, but does not alter inflammatory biomarkers in patients with peripheral artery disease: A systematic review and meta-analysis. Journal of Cardiovascular Translational Research. Advance online publication. https://doi.org/10.1007/s12265-023-10451-0